CSR and Financial Fraud: Board Gender and Audit Committee Expertise as Moderating - Ofii Fatul Lathiifah; Fuad Fuad (Jurnal Proaksi, 2024)
Financial statement fraud negatively impacts for the company, both materially and immaterially, including reduced stakeholders trust. The highlights the need for transparency through CSR reports. CSR represent the company’s transparency and reduce fraud. However, oportunistic managers may exploit CSR as a tool to conceal fraudulent actions. This study aimed to analyze the relationship between CSR disclosure and financial statement fraud, as well as the moderating effects of gender diversity on boards of commissioners and committee expertise. This study is a quantitative approach with a population of state-owned companies listed on IDX from 2019 to 2023. The sampling technique was purposive sampling, which resulted in 20 companies. The analysis methods were panel data logistic regression and MRA using the Eviews 12 software. The results indicated that CSR disclosure positively influences financial statement fraud. Gender diversity on the board does not moderate this relationship, while audit committee with financial expertise weakens the relationship between CSR disclosure and financial statement fraud. The findings contribute to agency theory and provide practical implications for companies and investors in identifying potential fraud related to CSR activities. The novelty of this research is the addition of two moderating variables.